Factors associated with unfavourable treatment outcomes among patients with Multidrug-resistant Tuberculosis receiving outpatients care - Maria Jose Vadakunnel; Vijayalakshmi Jawaharlal Nehru; Usharani Brammacharry; Venkateswari Ramachandra; Suganthi Palavesam; Anbazhagi Muthukumar; Balasundaram Revathi Mani; Gunavathy Pradhabane; S. R. Sriramkumar; Kanagavel Venkatchalam; Muthuraj Muthaiah (Scientific Reports)
Abstract Enhancing treatment outcomes for drug-resistant tuberculosis is a major global priority for tuberculosis control programs. India has the highest number of Multidrug-resistant Tuberculosis cases worldwide, yet no longitudinal studies have assessed the factors affecting treatment outcomes in public sector conditions. This study aimed to evaluate factors associated with ineffective treatment outcomes in patients with Multidrug-resistant Tuberculosis receiving outpatient care under the National Tuberculosis Elimination Programme in Puducherry, India, from January 2020 to December 2023. We employed multivariate regression methods to calculate odds ratios with 95% confidence intervals to identify factors linked to unsuccessful treatment outcomes. Clinical data from patients with Multidrug-resistant Tuberculosis revealed an overall treatment success rate of 60.42%. The findings showed that patients undergoing retreatment were more likely to experience unsuccessful outcomes. Additionally, co-infection with HIV, as well as the use of alcohol or tobacco, increased the odds of treatment failure. Patients with heteroresistant patterns had 2.72 times higher odds of unsuccessful treatment outcomes compared to those with inferred and true-resistant patterns. Furthermore, patients living in rural areas typically experienced worse treatment outcomes than those in urban areas, with higher rates of loss to follow-up. Patients on longer treatment regimens were also more likely to be lost to follow-up compared to those on shorter regimens. Notably, true resistance due to rpoB gene mutations accounted for 65.9% (29 out of 44) of total deaths, with mutations at codon S450L contributing to 47.7% of these fatalities, a finding that has not been reported elsewhere. The study highlighted a strong association between heteroresistance in the rpoB gene and poor treatment outcomes. These results emphasize the need for detailed molecular-level studies to improve treatment outcomes by ensuring appropriate drug selection for MDR/RR Tuberculosis. Additionally, further research is necessary to determine the impact of heteroresistance on treatment outcomes in individual patients.